Cross-country and historical variation in alcohol consumption among older men and women: Leveraging recently harmonized survey data in 21 countries. (1st October 2020) - Calvo, Esteban; Medina, José T.; Ornstein, Katherine A.; Staudinger, Ursula M.; Fried, Linda P.; Keyes, Katherine M.
Highlights: Alcohol-related morbidity and mortality is greater at older than younger age. Older adults' alcohol consumption data were harmonized across countries and time. Alcohol consumption patterns vary widely across countries and historical time. Later life alcohol consumption is increasing in most but not all countries. Variation across gender and age reflects both physiological and social determinants. Abstract: Background: Alcohol consumption causes greater harm in older than younger adults. As the population ages, understanding cross-country and time-varying drinking patterns of older adults is of critical importance. Available evidence relies primarily on ecological data. Methods: We harmonized survey data for 179, 881 adults age 50+ observed repeatedly between 1998 and 2016 in 21 countries. Next, we estimated historical variation in consumption across countries (overall and stratified by gender and age group 50−64/65+). Results: On average, 51.95 % of older adults consumed any alcohol over the observed period. For 13 countries, the proportion of older adults who drink increased (mean annual increase: 0.76 percent points). Heavy drinking (men drinks/day>3 or binge>5, women drinks/day>2 or binge>4) peaked at 23.54 % for England in 2010 and lifetime abstainers at 69.65 % for China in 2011. Across countries and among drinkers, consumption frequency was 2.57 days/week, the number of standard drink units when drinking was 2.57, and the average number of drinks/day over a week was 1.12. Consumption patterns varied substantially across countries and historical time. Overall probability and frequency of consumption were higher in men than women, with the largest gaps observed in 2011 for China, but gender gaps decreased (even reversed) in the young old and varied across country and time. Conclusions: Wide variation in older adults' alcohol consumption across countries and time suggests that broad scale prevention and intervention efforts can be harnessed for potential population-level health benefits. Further variation by gender and age reflect physiological and social factors simultaneously shaping alcohol consumption.